Current Endocardial Approaches for Left Atrial Appendage Closure. (2019) - Rocca, Domenico G Della; Prete, Armando Del; Biase, Luigi Di; Horton, Rodney P; Al-Ahmad, Amin; Bassiouny, Mohamed; Mohanty, Sanghamitra; Trivedi, Chintan; Romero, Jorge; Gianni, Carola; Burkhardt, J David; Gallinghouse, G Joseph; et al.
No abstract available